GLP-1 attenuates intestinal fat absorption and chylomicron production via vagal afferent nerves originating in the portal vein - Simon Hoffman; Danielle Alvares; Khosrow Adeli (Elsevier, 2022)
Background/Objective: GLP-1R agonists have been shown to reduce fasting and postprandial plasma lipids, both of which are independent risk factors for the development of cardiovascular disease. However, how endogenous GLP-1 - which is rapidly degraded - modulates intestinal and hepatic lipid metabolism is less clear. A vagal gut-brain-axis originating in the portal vein has been proposed as a possible mechanism for GLP-1's anti-lipemic effects. Here we sought to examine the relationship between vagal GLP-1 signalling and intestinal lipid absorption and lipoprotein production. Methods: Syrian golden hamsters or C57BL/6 mice received portal vein injections of GLP-1(7-36), and postprandial and fasting plasma TG, TRL TG, or VLDL TG were examined. These experiments were repeated during sympathetic blockade, and under a variety of pharmacological or surgical deafferentation techniques. In addition, hamsters received nodose ganglia injections of a GLP-1R agonist or antagonist to further probe the vagal pathway. Peripheral studies were repeated in a novel GLP-1R KO hamster model and in our diet-induced hamster models of insulin resistance. Results: GLP-1(7-36) site-specifically reduced postprandial and fasting plasma lipids in both hamsters and mice. These inhibitory effects of GLP-1 were investigated via pharmacological and surgical denervation experiments and found to be dependent on intact afferent vagal signalling cascades and efferent changes in sympathetic tone. Furthermore, GLP-1R agonism in the nodose ganglia resulted in markedly reduced postprandial plasma TG and TRL TG, and fasting VLDL TG and this nodose GLP-1R activity was essential for portal GLP-1s effect. Notably, portal and nodose ganglia GLP-1 effects were lost in GLP-1R KO hamsters and following diet-induced insulin resistance. Conclusion: Our data demonstrates for the first time that portal GLP-1 modulates postprandial and fasting lipids via a complex vagal gut-brain-liver axis. Importantly, loss or interference with this signalling axis via surgical, pharmacological, or dietary intervention resulted in the loss of portal GLP-1s anti-lipemic effects. This supports emerging evidence that native GLP-1 works primarily through a vagal neuroendocrine mechanism.